Analisis terhadap Dualitas Peraturan Menteri dalam Sistem Peraturan Perundang-Undangan di Indonesia - Irfan Ardyan Nusanto (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
This article examines the duality of ministerial regulations in Indonesian regulation system based on their making authority sources according to Law No. 12 Year 2011 concerning Regulation Making Rules (UU P3). The approach methods used in this research are conceptual approach and statute approach. This article concludes there are two ministerial regulations which recognized as regulations by UU P3 that should be distinguished. Ministerial regulation which was made by higher regulations order (delegated legislation) could be categorized as an implementing rule (verordnung). Whereas, ministerial regulation which was made based on ministery position authority (inherent aat het bestuur) could be categorized as a beleidsregel, standing as policy rules. Though, the two of them were recognized as regulations, however, they have different design, background and character, thus, their substance, binding power, hierarchy position and review mechanism, were not the same. Therefore, ministerial regulation which was beleidsregel could not be applied as the same as implementing regulation (verordnung).